2006
DOI: 10.1002/ejic.200500875
|View full text |Cite
|
Sign up to set email alerts
|

In situ HT‐XRD Study on the Formation of Hexagonal Ammonium Tungsten Bronze by Partial Reduction of Ammonium Paratungstate Tetrahydrate

Abstract: Keywords: Tungsten / Reduction / In situ studies / X-ray diffraction / X-ray photoelectron spectroscopy / Solid-state 1 H NMR spectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 48 publications
1
31
0
1
Order By: Relevance
“…Previously AMT [1,33,38,[47][48][49][50][51][52] or a structure close to AMT [38] was said to be a decomposition product of APT at 240 °C. Based on these, it was unknown whether the decomposition of AMT would be the same as the decomposition of APT above 240 °C, or it would differ significantly.…”
Section: Comparison Of the Thermal Behavior Of Amt And Aptmentioning
confidence: 99%
“…Previously AMT [1,33,38,[47][48][49][50][51][52] or a structure close to AMT [38] was said to be a decomposition product of APT at 240 °C. Based on these, it was unknown whether the decomposition of AMT would be the same as the decomposition of APT above 240 °C, or it would differ significantly.…”
Section: Comparison Of the Thermal Behavior Of Amt And Aptmentioning
confidence: 99%
“…On the other hand, X-ray phase analysis has revealed that diffraction pattern of WP sample after heating at 375°C comprises a set of diffraction reflections which can be attributed to hexagonal WO 3 (h-WO 3 , PDF 04-007-2322) and monoclinic WO 3 (m-WO 3 , PDF 00-043-1035) [10][11][12]. We can't exclude, however, content of hexagonal ammonium tungsten bronze (NH 4 ) 0.33-x WO 3-y (HATB, PDF 00-058-0151) in this sample because there is no sharp division of diffraction reflections between h-WO 3 and HATB [10,13,14]. Powder diffraction pattern of WP sample heated at 600°C comprised only diffraction reflections characteristic for monoclinic WO 3 [10][11][12]14].…”
Section: Resultsmentioning
confidence: 96%
“…W O 3 powders prepared from the reference APT and from hexagonal ammonium tungsten bronze (HATB, (NH4) 0.33-x WO 3-y ) were used as precursors in the solid-gas phase reactions. HATB was obtained by heating APT at 400 °C in H 2 for 6h [38]. The precursor tungsten oxides with different compositions (oxidized or partially reduced), structures (monoclinic (m-WO 3 ) or hexagonal (h-WO 3 )) and particle sizes (70-90 or 100-300 nm) were prepared by thermal decomposition from APT or HATB by controlling the annealing temperature and atmosphere [39].…”
Section: Preparation Of the Wo 3 Starting Materialsmentioning
confidence: 99%